IMPLEMENTASI CHATBOT BASED LEARNING UNTUK MELATIH KETERAMPILAN MENULIS PUISI PESERTA DIDIK SMP - Batitusta, Fabian Omar; Asteria, Prima Vidya; Yuniseffendri (JURNAL SKRIPTA, 2025)
Poetry writing learning at the junior high school level often faces various challenges. One of these challenges is the low interest and creativity of students in learning poetry. This phenomenon is caused by conventional learning methods that offer limited interaction. However, along with technological advancement, chatbot-based learning has emerged as an innovative solution to create a more personalized, interactive, and adaptive learning experience tailored to students’ needs. This study aims to analyze the implementation of chatbot-based learning in developing junior high school students’ poetry writing skills as well as to identify its benefits and challenges. The study employed a qualitative approach using a literature review method through a systematic search of scientific articles published within the last ten years on Google Scholar. The collected data were analyzed thematically and deductively to identify patterns of implementation, potential, and obstacles in using chatbots for poetry writing instruction. The findings show that integrating chatbots into poetry writing learning offers various benefits, such as enhancing learning personalization, learner autonomy, engagement, and creativity through rapid feedback and flexible writing practice. In addition, chatbots assist teachers in reducing administrative workloads and focusing more on creative guidance. Overall, this study concludes that chatbot-based learning has great potential to improve the effectiveness and quality of poetry writing instruction at the junior high school level.